Ta'awun Values in the Process of Collecting the Qur'an: Inspiration for Inclusive and Equitable Sharia Economic Development - Adri Adri; Ferdi Prayoga; Pujy Yonesha; Fadhilla Husna; Awaluddin Awaluddin (Proceeding of The International Conference on Business and Economics, 2025)
This paper examines the implementation of the value of ta'awun (cooperation) in the process of collecting the Qur'anic manuscripts during the time of the companions as an inspiration for the development of an inclusive and equitable sharia economy. The collection of the Qur'anic manuscripts was a collective effort involving the companions, qira'at experts, and writers of revelation to maintain the purity of revelation and prevent division of the Muslim community. The value of cooperation reflected in the process is in line with the basic principles of sharia economics such as distributive justice, empowerment of the community, and inclusiveness. By using the library research method with a descriptive analysis approach, this study found that the application of the value of ta'awun can strengthen sharia economic practices through a fair partnership model and investment oriented towards collective welfare. In addition, this value also encourages the creation of an economic system that is not only based on efficiency, but also on ethics and sustainability. Thus, this study provides a conceptual contribution in linking Islamic traditions with contemporary economic practices, creating a harmonious ecosystem between spiritual values and material goals.